Perplexing Polyphenolics: The Isolations, Syntheses, Reappraisals, and Bioactivities of Flavonoids, Isoflavonoids, and Neoflavonoids from 2016 to 2022 - Syed Muhammad Umer; Shahbaz Shamim; Khalid Mohammed Khan; Rahman Shah Zaib Saleem (Life, 2023)
Flavonoids, isoflavonoids, neoflavonoids, and their various subcategories are polyphenolics–an extensive class of natural products. These compounds are bioactive and display multiple activities, including anticancer, antibacterial, antiviral, antioxidant, and neuroprotective activities. Thus, these compounds can serve as leads for therapeutic agents or targets for complex synthesis; they are coveted and routinely isolated, characterized, biologically evaluated, and synthesized. However, data regarding the compounds’ sources, isolation procedures, structural novelties, bioactivities, and synthetic schemes are often dispersed and complex, a dilemma this review aims to address. To serve as an easily accessible guide for researchers wanting to apprise themselves of the latest advancements in this subfield, this review summarizes seventy-six (76) articles published between 2016 and 2022 that detail the isolation and characterization of two hundred and forty-nine (249) novel compounds, the total and semisyntheses of thirteen (13) compounds, and reappraisals of the structures of twenty (20) previously reported compounds and their bioactivities. This article also discusses new synthetic methods and enzymes capable of producing or modifying flavonoids, isoflavonoids, or neoflavonoids.